Multilingual and Multi-Generational Italian Identity in a Netflix Series: Subtitling Generazione 56k (2021) into English - Manfredi, Marina; Bartolini, Chiara (Íkala, Revista de Lenguaje y Cultura, 2023)
This paper reports an investigation into the representation of “Italianness” in the recent Netflix Italian series Generazione 56k, which was exported to English-speaking countries. This series deals with characters from different generations and displays regional varieties. This qualitative study examined the macro- and micro-strategies used in the creation of English subtitles for the first season. The focus is on key functions of telecinematic discourse, i.e., characterisation, realism, and humour, realised through the use of (a) multilingualism in the broadest sense, including geographical dialects, and (b) multi-generational language (colloquialisms, “unconventional language”, particularly, teenage and youth language, and taboo). Findings reveal a tendency towards neutralisation strategies in the English subtitles. Even considering the constraints inherent in the subtitling mode, these strategies do not successfully represent “Italianness” with its local geographical diversity, and only partially convey the representation of multi-generational language, also affecting humour. The themes engaging millennials, however, are expressed and might be appreciated by an international audience. In the light of our analysis and conclusions, it may be interesting to understand whether younger generations, increasingly accustomed to “multilingualism” especially in Netflix programmes, would also envisage a different subtitling experience.